Psychedelic integration: An analysis of the concept and its practice - Bathje, Geoff J.; Majeski, Eric; Kudowor, Mesphina (Frontiers in Psychology, 2022)
The concept of integration has garnered increased attention in the past few years, despite a long history of only brief mention. Integration services are offered by therapists, coaches, and other practitioners, or may be self-guided. There are many definitions of psychedelic integration, and the term encompasses a range of practices and techniques. This seems to have led to confusion about what integration is and how it is best practiced. The primary focus of this paper is the presentation of the first extensive review and concept analysis of definitions, practices, and models of psychedelic integration. We provide a synthesized definition of integration, synthesized model of integration, and comprehensive summary of integration practices to bring clarity to the subject.